The Influence of Bank Health and Interest Rates on Bank Profitability and Moderated By Economic Growth - Nikmatul Rochmah; Puji Endah Purnamasari (Universitas Batanghari Jambi, 2023)
His research aims to determine the effect of bank soundness and interest rates on the profitability of banking companies listed on the Indonesia Stock Exchange in 2018-2021 and moderated by economic growth. The data type used is secondary data from banking financial reports, BI Rate data, and GDP data for 2018-2021. The sampling technique used was purposive sampling, and 21 samples were obtained from conventional commercial banks. The data analysis technique uses panel data regression analysis, and MRA uses E-views 12 software. The results of this study are that partially, the soundness of the bank as measured by the RGEC method affects, but only the Good Corporate Governance and Earning factors. However, the Risk Profile and Capital factors have no effect, so interest rates have a negative effect on profitability. For the bank health moderation test, only the CAR factor can be moderated by economic growth